The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/app.42977
|View full text |Cite
|
Sign up to set email alerts
|

Cooling rate dependence of the crystallinity at nonisothermal crystallization of polymers: A phenomenological model

Abstract: The cooling rate dependence of the crystallinity of polymers is investigated via the example of different technical polypropylenes using fast scanning calorimetry (FSC) in a cooling rate range between 1 and 5000 K s 21 . In the slower cooling rate range (below 100 K s 21 ) the crystallinity increases slightly with decreasing cooling rate. Above cooling at 100 K s 21 the crystallinity decreases substantially and vanishes at the critical cooling rate. We describe this behavior using a simplified model with two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…As mentioned before, it is suggested that secondary crystallization proceeds only at slow cooling rates. Note, in the previous study, the cooling rate dependence of the crystallinity was described using a simple phenomenological model with generic crystallization function and retardation function . The form of the functions is different from the present equation.…”
Section: Nonisothermal Crystallizationmentioning
confidence: 89%
“…As mentioned before, it is suggested that secondary crystallization proceeds only at slow cooling rates. Note, in the previous study, the cooling rate dependence of the crystallinity was described using a simple phenomenological model with generic crystallization function and retardation function . The form of the functions is different from the present equation.…”
Section: Nonisothermal Crystallizationmentioning
confidence: 89%
“…Under the high supercooling (low curing temperature), there was not enough time to adjust the crystal structure between the PA 6 molecular chains; consequently, the amorphous structure was formed. In contrast, under low supercooling, a more stable crystal structure was formed . Therefore, the degree of crystallinity of PA 6 increased in proportion to the curing temperature.…”
Section: Resultsmentioning
confidence: 95%
“…The crystallinity was calculated by measuring the melting enthalpy and comparing that with the melting enthalpy of 100% crystalline PCL, as reported in the literature . In general, the degree of crystallinity as the polymer melt cools down below the melting point during electrospinning due to convective heat loss may depend on the cooling rate experienced by the polymer . Faster cooling rates reduce the time that crystals are allowed to form, and it may lead to reduced crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…[52] In general, the degree of crystallinity as the polymer melt cools down below the melting point during electrospinning due to convective heat loss may depend on the cooling rate experienced by the polymer. [53] Faster cooling rates reduce the time that crystals www.advancedsciencenews.com www.mme-journal.de are allowed to form, and it may lead to reduced crystallinity. Thus, thinner fibers might be at a disadvantage due to their higher surface to volume ratio which increases the rate of heat loss.…”
Section: Effect Of Spinneret Architecture On Crystallinitymentioning
confidence: 99%